KINERJA GURU DALAM PERSIAPAN PEMBELAJARAN UNTUK TRANSISI PAUD KE SD YANG MENYENANGKAN - Febiola Lutfansyah, Karina (Lembaga Penelitian dan Pengabdian Institut Kariman Wirayudha Sumenep, 2025)
The transition from PAUD to SD is a new policy approved by the Ministry of Education and is also a movement for change pursued by the government for educational institutions. In order to achieve the success of the policy objectives, the readiness of teachers and educational institutions has an important role because the school must provide good and sufficient facilitation for students so that the educational process occurs in accordance with its standards. With this pleasant PAUD to SD transition policy, teachers are expected to be able to manage and provide education in accordance with teacher performance indicators during the PAUD to SD transition period. This research is a qualitative descriptive study with research methods, namely observation, interviews and documentation. The data analysis technique in the research uses the Miles and Huberman model where the model has 4 stages, namely data collection, data reduction, data presentation and drawing conclusions. Then the data validity test was carried out by triangulating the data with many source.